2017
DOI: 10.1037/cns0000114
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive daydreaming: Proposed diagnostic criteria and their assessment with a structured clinical interview.

Abstract: Daydreaming, a common mental activity, can be excessive and accompanied by distress and impaired functioning in daily life. Although currently not formally identified by diagnostic manuals, daydreaming disorder (maladaptive daydreaming [MD]) is a clinically well-defined phenomenon. However, research is lacking regarding the diagnostic reliability of MD. Our aims were (a) to develop diagnostic criteria and a structured interview for MD, (b) to examine the reliability of this measure for distinguishing individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(94 citation statements)
references
References 28 publications
1
93
0
Order By: Relevance
“…Criterion-related evidence for the MDS-16 was demonstrated by its high correlation, r ¼ .58, p ¼ .01, with the most closely related criterion measure: the Creative Experiences Questionnaire, an instrument derived from measures of fantasy proneness (Merckelbach, Harselenbergm, & Muris, 2001; see later). Somer, Soffer-Dudek, Ross, & Halpern, (2017) also reported that the MDS-16 discriminated well between self-identified individuals with and without MD and demonstrated solid internal consistency and temporal stability (test-retest reliability, r ¼ .92). The MDS has previously shown excellent sensitivity (95%) and high specificity (89%) levels.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…Criterion-related evidence for the MDS-16 was demonstrated by its high correlation, r ¼ .58, p ¼ .01, with the most closely related criterion measure: the Creative Experiences Questionnaire, an instrument derived from measures of fantasy proneness (Merckelbach, Harselenbergm, & Muris, 2001; see later). Somer, Soffer-Dudek, Ross, & Halpern, (2017) also reported that the MDS-16 discriminated well between self-identified individuals with and without MD and demonstrated solid internal consistency and temporal stability (test-retest reliability, r ¼ .92). The MDS has previously shown excellent sensitivity (95%) and high specificity (89%) levels.…”
Section: Methodsmentioning
confidence: 80%
“…Responses on the MDS-16 are indicated on a scale ranging from 0% (never) to 100% (extremely frequent), with 10% increments. Overall score is the average of all item responses, with higher scores indicating higher MD behaviors, and a cutoff score of 50 distinguishing between maladaptive daydreamers and nonmaladaptive daydreamers (Somer, Soffer-Dudek, Ross, & Halpern, 2017). Criterion-related evidence for the MDS-16 was demonstrated by its high correlation, r ¼ .58, p ¼ .01, with the most closely related criterion measure: the Creative Experiences Questionnaire, an instrument derived from measures of fantasy proneness (Merckelbach, Harselenbergm, & Muris, 2001; see later).…”
Section: Methodsmentioning
confidence: 99%
“…Interactions between sensory and cognitive cues might play important roles that require future investigations. Exploring these interactions might help clarify issues, like, for instance, why maladaptive daydreaming, a condition with highly vivid experiences that can absorb the individual eliciting compulsive daydreaming and leading to impaired functioning [171][172][173], is nevertheless experienced as being internally generated. It might be the case that cognitive cues regarding the certain degree of voluntary control in the initiation and/or maintenance of episodes of mind-wandering [174] that is present in maladaptive daydreaming have a crucial part in signalling internal generation to the reality monitoring system despite the highly amplified sensory characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…As detailed above, this 16-item measure assesses four aspects of abnormal daydreaming: the extent to which one consistently feels drawn to daydreaming and has a strong, addictive urge to engage in daydreaming (yearning); the extent to which one feels that engaging in daydreaming impairs their functioning in social, academic, or vocational domains and interferes both with wide-ranging life goals and with specific daily chores or tasks (impairment); the extent to which one finds oneself engaging in physical movement associated with daydreaming such as accompanying facial expressions, mouthing the words, rocking, or pacing (kinesthesia); and the extent to which one uses music to initiate or maintain the daydreaming experience (music). The scale is reliable (Schimmenti, Sideli, La Marca, Gori, & Terrone, 2019;Somer, Lehrfeld, et al, 2016;Somer, Soffer-Dudek, Ross, & Halpern, 2017) and is measured on an 11-point scale, ranging from 0% (e.g., never, no distress at all) to 100% (e.g., extremely frequent, extreme distress). In the present study, Cronbach's alpha for the 16 items on the final 4-country sample was 0.95, with 0.93, 0.96, 0.96, and 0.92 for the American, Italian, Turkish, and the British samples, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Maladaptive Daydreaming (MD) is a recently proposed mental disorder, defined as a persistent and recurrent absorption in detailed fantastic imagery, to the point where it becomes a type of behavioral addiction, causing distress and impairing functioning in various life domains such as social relations or work (Pietkiewicz, Nȩcki, Ba nbura, & Tomalski, 2018;Schupak & Rosenthal, 2009;Somer, 2002). Diagnostic criteria include annoyance when being unable to daydream and repeated unsuccessful efforts to control, cut back, or stop daydreaming (Somer, Soffer-Dudek, Ross, & Halpern, 2017). Indeed, behavioral addictions involve elements of impulsecontrol symptoms alongside obsessive-compulsive symptoms (Demetrovics & Griffiths, 2012;Karim & Chaudhri, 2012;Robbins & Clark, 2015), and as such, involve both elements of risk aversion (negative reinforcement) and sensation-seeking (positive reinforcement) (Robbins & Clark, 2015), both of which are present in MD (Soffer-Dudek & Somer, 2018;Somer, 2002;Somer, 2018).…”
Section: Introductionmentioning
confidence: 99%